Search for central exclusive production of top quark pairs in proton-proton collisions at $$ \sqrt{s} $$ = 13 TeV with tagged protons - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Bergauer, Thomas; Chatterjee, Suman; Damanakis, Konstantinos; Dragicevic, Marko; Escalante Del Valle, Alberto; Hussain, Priya Sajid; Jeitler, Manfred; Krammer, Natascha; Lechner, Lukas; et al. (Springer Science and Business Media LLC, 2024)
Abstract A search for the central exclusive production of top quark-antiquark pairs ( $$ \textrm{t}\overline{\textrm{t}} $$ t t ¯ ) is performed for the first time using proton-tagged events in proton-proton collisions at the LHC at a centre-of-mass energy of 13 TeV. The data correspond to an integrated luminosity of 29.4 fb −1. The $$ \textrm{t}\overline{\textrm{t}} $$ t t ¯ decay products are reconstructed using the central CMS detector, while forward protons are measured in the CMS-TOTEM precision proton spectrometer. An observed (expected) upper bound on the production cross section of 0.59 (1.14) pb is set at 95% confidence level, for collisions of protons with fractional momentum losses between 2 and 20%.
Keywords: electron; p p: scattering; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; GeV-cms; FOS: Physical sciences; bottom: particle identification; QC770-798; channel cross section: upper limit; High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); Hadron-Hadron Scattering; Top Physics; Nuclear and particle physics. Atomic energy. Radioactivity; muon; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; High energy physics; info:eu-repo/classification/ddc/530; Hadron-Hadron Scattering; p: spectrometer; PARTICLE PHYSICS; LARGE HADRON COLLIDER; CMS; CMS; final state: ((n)jet dilepton); Physics; ddc:530; Top Physics; LARGE HADRON COLLIDER; top: exclusive production; CERN LHC Coll; Hadron-Hadron Scattering; Top Physics; PARTICLE PHYSICS; LHC; Experimental particle physics; top: pair production; jet: bottom; p p: colliding beams; experimental results